Ministry Of Higher Education and Scientific Research Authored Under Copyright Protection Law No. 3 Of 1971: (Comparative Analytical Study) - Adnan Hashem Jawad Al-Sharoufi (Journal of Legal Sciences, 2024)
The topic of copyright protection is one of the very important topics as it is an effective tool in the development of the state in all its scientific, artistic and literary aspects. The premise of our research revolves around the extent to which the Ministry of higher education and scientific research can become an author and thus can contribute to the development of a central plan for the advancement of scientific, artistic and literary works as they represent an important pillar in intellectual property and can open branches in universities, institutes and research centers. It is expected that the outputs will be qualitative and scientific fruitful contribute to the advancement of all fields. Therefore, it was necessary to distribute the topic to two researchers, the first of which is to research the collective work, considering that the collective work represents one of the means for the ministry to receive copyright, and in the second requirement, we will highlight the joint work as a second means for the ministry to receive copyright.